Stosunki prawne pomiędzy organami przedstawicielstwa pracowniczego w przedsiębiorstwie państwowym - Sypniewski, Zbigniew (Wydział Prawa i Administracji UAM, 1988)
According to legal writers, subjects of legal relations in the analysed sphere are a crew and a trade union, not their organs. However, self-government and trade union organs have various duties and rights which to some extent are independent of the duties and rights of the organizations they represent. The above justifies treating those organs as legal subjects, capable of entering upon reciprocal legal relations. Such an approach is of great practical importance. Legal relations between organs of employees' representation are the relations of cooperation, based on law, statutes and contracts. Those relations are entered upon by virtue of the law and their changes may be of general or individual character. They are terminated only when one of the participating subjects has ceased to exist. The contents of legal relations of cooperation includes two types of rights and duties, i.e. the rights and duties which are addressed 1) directly to organs; 2) to a crew or to a trade union organization, yet the circumstances make it clear that the organs have to behave in a certain way. Form a substantive point of view those rights and duties are concerned with creating or applying legal norms in an enterprise.
Legal relations between organs of the employees' representation in a state enterprise